2020
DOI: 10.3390/ijerph17207561
|View full text |Cite
|
Sign up to set email alerts
|

Older Adults’ Gender, Age and Physical Activity Effects on Anxiety, Optimism, Resilience and Engagement

Abstract: The purpose of the study was to understand the effects of gender and age on anxiety, optimism, resilience and engagement in a group of older adults. An observational, quantitative, descriptive and transversal design was used with non-probabilistic sampling. Descriptive statistical analyses, reliability tests (Cronbach’s alpha) and linear correlation tests (Pearson’s) were performed, and the development of multivariate linear regression models was conducted. Female participants in the sample had higher levels i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 49 publications
4
15
0
Order By: Relevance
“…The result in Table 1 also implied that teachers of advanced age are less optimistic than younger teachers. This result is corroborated with the findings of the study conducted by Mishra (2013) and Martinez-Moreno, et al (2020), which revealed that younger adults are more optimistic than older ones. One possible reason for this is that older teachers are more vulnerable to the virus than younger adults.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…The result in Table 1 also implied that teachers of advanced age are less optimistic than younger teachers. This result is corroborated with the findings of the study conducted by Mishra (2013) and Martinez-Moreno, et al (2020), which revealed that younger adults are more optimistic than older ones. One possible reason for this is that older teachers are more vulnerable to the virus than younger adults.…”
Section: Resultssupporting
confidence: 89%
“…This result is supported by several studies which have claimed female workers tend to report a higher level of stress and burnout at work (Marchand et al, 2018;Purvanova & Muros, 2010). The probable reason for the high level of COVID-19 related job stress among female teachers is that females tend to be more anxious than males in times of distress, as indicated in several literature reviews (Hou et al, 2020;Martinez-Moreno et al, 2020). However, based on Table 2, male teachers have felt more emotionally exhausted than female teachers due to COVID -19.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…The effect of PA has been inquired in different ages of people such as children [35][36][37], adolescents [37][38][39][40], middle-aged people [41,42] and older adults [43][44][45][46]. There have also been studies on different populations, for instance, pregnant women and mothers [47,48], nurses [49], patients [50][51][52][53][54], and people with overweight/obesity [55,56].…”
Section: The Present Study and Hypothetical Modelmentioning
confidence: 99%
“…Sport research related to stress and well-being factors has been widely developed in recent years (López, 2015;Barbosa and Urrea, 2018), considered as important in different sports (Moreno-Murcia et al, 2006;Cano et al, 2019). Previous studies have highlighted the importance of optimism as a facilitating aspect of resilience (Ferrando et al, 2002;Aranzana et al, 2016;Martínez-Moreno et al, 2020), and competitive stress as a possible inducer of specific development in sport training stages, while also predicting how combinations of other variables could influence the athlete. It is the resilience and optimism of the individual coping strategies, which the athlete uses, that most help him or her (Galli and Vealey, 2008;Fletcher and Sarkar, 2012;García et al, 2014).…”
Section: Introductionmentioning
confidence: 99%